2004
DOI: 10.1207/s15326942dn2501&2_10
|View full text |Cite
|
Sign up to set email alerts
|

Attention Deficit Hyperactivity Disorder Symptoms and Response Inhibition After Closed Head Injury in Children: Do Preinjury Behavior and Injury Severity Predict Outcome?

Abstract: We examined the effect of closed head injury (CHI) on the development of symptoms of secondary attention deficit hyperactivity disorder (SADHD), emotional disturbance, and impaired response inhibition. We also investigated the relation of developmental and recovery variables to SADHD symptoms and inhibition. Participants were 200 children aged 5-17 years, 137 children who had CHI, and 63 children with no history of CHI served as controls. We assessed preinjury behavior problems, head injury variables (severity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
55
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 52 publications
4
55
0
Order By: Relevance
“…It permits voluntary control over responses in the presence of changing intentions, external cues or performance errors. Inhibitory control plays an important role in normal and abnormal development (e.g., Harnishfeger & Pope, 1996;Nigg, 2000;Radvansky, Zacks, & Hasher, 2005;Williams, Ponesse, Schachar, Logan, & Tannock, 1999) and deficits in inhibition are implicated in the effects of brain pathology (Aron, Fletcher, Bullmore, Sahakian, & Robbins, 2003a;Aron & Poldrack, 2005a;Schachar, Levin, Max, Purvis, & Chen, 2004). Deficient inhibition is considered to be one of the central cognitive abnormalities in attention deficit hyperactivity disorder (ADHD) and to be related to its underlying neuropathology (Barkley, 2001;Willcutt, Doyle, Nigg, Faraone, & Pennington, 2005).…”
mentioning
confidence: 99%
“…It permits voluntary control over responses in the presence of changing intentions, external cues or performance errors. Inhibitory control plays an important role in normal and abnormal development (e.g., Harnishfeger & Pope, 1996;Nigg, 2000;Radvansky, Zacks, & Hasher, 2005;Williams, Ponesse, Schachar, Logan, & Tannock, 1999) and deficits in inhibition are implicated in the effects of brain pathology (Aron, Fletcher, Bullmore, Sahakian, & Robbins, 2003a;Aron & Poldrack, 2005a;Schachar, Levin, Max, Purvis, & Chen, 2004). Deficient inhibition is considered to be one of the central cognitive abnormalities in attention deficit hyperactivity disorder (ADHD) and to be related to its underlying neuropathology (Barkley, 2001;Willcutt, Doyle, Nigg, Faraone, & Pennington, 2005).…”
mentioning
confidence: 99%
“…However, the relatively small number of youths with a TBI may have limited the investigation’s ability to detect significant associations. Some (57,58) but not all (34) prior investigations have found equivalent rates of psychiatric symptoms among children with TBI and other kinds of injury. Anatomic differences in TBI symptom presentations may explain some of the observed variations in findings across investigations (59).…”
Section: Discussionmentioning
confidence: 94%
“…One recent large-scale epidemiologic investigation found that beyond its association with PTSD, exposure to trauma is associated with the development of other anxiety, depressive, substance use, and disruptive behavior disorders among children and adolescents (1). Smaller-scale investigations in subgroups of injured youths have also suggested that the symptoms of other anxiety, depressive, substance-related, and behavioral disturbances can occur in the wake of traumatic physical injury (2734). …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, several studies have shown that children with ADHD are less aware of errors. Typically, in neuropsychological tasks, they do not slow down response speed after commission errors, in contrast to normal control children (Schachar et al 2004;O'Connell et al 2009). This finding has been linked to abnormal fronto-striatal network function, especially to dysfunction of the anterior cingulate cortex (Liotti et al 2005;Albrecht et al 2008).…”
Section: Introductionmentioning
confidence: 93%